Role of M Cells in Human Mucosal Immunity to Mycobacterium tuberculosis. (4th October 2017) - Nair, Vidhya; Khan, Haaris; Mitchell, Ron; Shiloh, Michael U
Abstract: Background: Mycobacterium tuberculosis (Mtb), the causative agent of tuberculosis (TB), is a bacterial pathogen that infects roughly one-third of the worldÕs population and causes 1–2 million deaths per year. The current paradigm is that phagocytosis of Mtb by patrolling alveolar macrophages initiates Mtb infection. While this model can account for pulmonary TB, it does not adequately explain the occurrence of extrapulmonary forms of TB that manifest in the absence of obvious lung involvement, such as tuberculous cervical lymphadenitis, also known as scrofula. We hypothesized that specialized epithelial cells called microfold cells (M cells) may be an alternate portal of entry for Mtb. Previously we demonstrated that Mtb is able to transcytose across an epithelial barrier in an M cell dependent manner and that M cell mediated transcytosis is vital for Mtb pathogenesis in a mouse model of tuberculosis. Methods: We used an in vitro M-cell mediated translocation assay and a Mtb mutant lacking a key virulence factor, ESAT6. We used biochemistry and genetics to identify a novel receptor for ESAT6. We also developed a novel explanted human adenoid Mtb infection model to study mucosal immunity. Results: We now demonstrate that the Mtb virulence factor ESAT6 is necessary and sufficient to mediate binding and transcytosis by M cells in vitro and in vivo, and that uptake of Mtb by M cells requires a unique cell surface ESAT6 receptor. We developed a novel explanted human adenoid model of M cell biology and demonstrate rapid Mtb transcytosis by primary human tissue within 60–120 minutes. Using flow cytometry we find that Mtb is first ingested by M cells and then after transcytosis, by tissue resident antigen-presenting cells. Explanted adenoids from 10 independent donors display a wide range of Mtb uptake. Conclusion: We conclude that Mtb ESAT6 is necessary for Mtb uptake by M-cells and that binding and transcytosis require a host receptor. Because explanted adenoids display a wide range of Mtb uptake, M cell mediated transcytosis may confer differential susceptibility to scrofula and disseminated disease. These findings are significant as M cells could potentially serve as the basis for novel therapeutic targets against primary Mtb infection. Disclosures: All authors: No reported disclosures.